Talent Wins: The New Playbook for Putting People First - Charan, Ram (Boston Harvard Business Review Press, 2018)
Provide expert insight and advice for what needs to change and how to change it, this is the definitive book for reimagining and creating a talent-driven organization that wins.
Keywords: Management - Talent